CO2-Reduktion im Verkehr - alle sind gefordert. - Kluge, Juliane; Stromberger, Rolf (Deutscher Verkehrs-Verl., 2007)
Die bisherige alleinige Verantwortung der Automobilindustrie zur CO2-Emissionsreduktion wird den sich verändernden Marktbedingungen nicht mehr gerecht. Die geteilte Verantwortung, der so genannte Integrated Approach, ist die kosteneffizienteste Vorgehensweise für eine nachhaltige CO2-Emissionsreduktion im Automobilsektor. difu

Due to the limited availability of fossil-based energy resources and the global trend of growing hothouse gas emission - notably so in the case of carbon dioxide (CO2) - long term mobility is most essential. The 'integrated approach' method in its entirety aims for a cost efficient and sustainable reduction in CO2 emission in the case of private cars. It is, therefore, most essential to coordinate efforts of all the parties concerned including politics (expansion of transport infrastructure, support for eco-driving) and the petroleum industry (admixture of bio fuel). This will help to achieve higher reductions in CO2 emission at correspondingly lower costs, compared with the adoption of purely vehicle technology-related measures. Against this background, the car manufacturing industry becomes more aware of its responsibilities and will thus be able to make its contribution to a sustainable reduction in CO2 emission. difu
Keywords: Verkehr; Schadstoff; Luftverunreinigung; Kohlendioxid; Kraftfahrzeug; Kraftfahrzeugindustrie; Kraftfahrzeugsteuer; Emissionsminderung; Fahrzeugtechnologie; Nachhaltigkeit; Kosteneffizienz; Kraftstoff; Fahrweise